2010
DOI: 10.1080/00480169.2010.65058
|View full text |Cite
|
Sign up to set email alerts
|

Development of a vaccine to mitigate greenhouse gas emissions in agriculture: Vaccination of sheep with methanogen fractions induces antibodies that block methane productionin vitro

Abstract: Antigens from methanogens are immunogenic in ruminants, and antisera from sheep vaccinated with fractions of methanogens have a significant impact on these organisms, inducing cell agglutination, and decreasing growth of methanogens and production of methane. Only antisera to selected methanogen fractions were able to achieve these effects. The results demonstrate the feasibility of a vaccination strategy to mitigate emission of methane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
54
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 25 publications
0
54
0
Order By: Relevance
“…Antisera were generated in sheep against these fractions and the ability of these antisera to inhibit methanogen growth and production of methane by in vitro pure cultures of M. ruminantium M1 was determined. Antisera against two of these M. ruminantium M1 fractions, a cytoplasmic fraction and a fraction prepared by extracting cell wall-derived proteins, reduced microbial growth and methane production (Wedlock et al, 2010). The results suggested that these fractions contained proteins that were immunogenic and had essential cellular functions that could be disrupted via interaction with antibodies.…”
Section: Methanogen Fractionsmentioning
confidence: 98%
See 3 more Smart Citations
“…Antisera were generated in sheep against these fractions and the ability of these antisera to inhibit methanogen growth and production of methane by in vitro pure cultures of M. ruminantium M1 was determined. Antisera against two of these M. ruminantium M1 fractions, a cytoplasmic fraction and a fraction prepared by extracting cell wall-derived proteins, reduced microbial growth and methane production (Wedlock et al, 2010). The results suggested that these fractions contained proteins that were immunogenic and had essential cellular functions that could be disrupted via interaction with antibodies.…”
Section: Methanogen Fractionsmentioning
confidence: 98%
“…High levels of avian (IgY) anti-methanogen antibodies were produced against cell preparations of methanogens, and addition of these antibodies to ruminal fluid in vitro resulted in a transient reduction of methane production from the cultures (Cook et al, 2008). Similarly, antisera from sheep vaccinated with sub-cellular fractions of M. ruminantium M1 inhibited methane formation by pure cultures of that species (Wedlock et al, 2010).…”
Section: Vaccines Targeting S Bovis and Lactobacillusmentioning
confidence: 99%
See 2 more Smart Citations
“…Vaccines against archaea have been successful in vitro (Wedlock et al, 2010) and are a very promising option that could be applied to all ruminants, even in grazing situations with little human contact. As there are currently no vaccines that are ready for practical application (Clark et al, 2004;Wright et al, 2004) and they are also discussed in another review at this meeting (Wedlock et al, 2013), they are excluded from this review.…”
mentioning
confidence: 99%